JUÁREZ IN THE CONSERVATIVE CHILEAN PRESS IN 1872 (Tzintzun, Revista de Estudios Históricos, 2016)
This text discusses how in the nineteenth century the conservative Catholic pressin Chile judged the politics of the mexican president Benito Juárez. On August 25,1872, with the news in Chile of the death of Juárez the daily El Independiente, withtendencies toward the conservative party, dedicated its editorial column to adiscussion of the defeat of Mexico and the conduct of the great man in the Reform.The portrait was harsh, negating Juárez hero status or that of patriotic defender inthe conception of his lack of republican virtues and tireless public ambition. Butmore than anything, they accused Juárez of squandering the opportunity ofconsolidating Mexico and its institutions after the defeat in 1867 of the Empire ofthe Archduke Maximiliano of Austria. In sum, Juárez was presented as a championof “revolutionary violence” that “devastated” “Spanish America” and Europe.
Keywords: Benito Juárez; presse catholique; l’Indépendant; libéralisme; Partie Conservateur